Entry Barriers and Opportunities for Fintechs in Open Banking Platforms - Mansour, Osama (The Hawaii International Conference on Systems Sciences, 2025)
The revised Payment Services Directive (PSD2) is reshaping traditional banking by requiring banks to grant licensed third-party providers (TPPs) access to customer data. This paper explores PSD2’s impact on Fintech market entry, assessing both opportunities and ongoing structural barriers. Through a qualitative investigation, it identifies key barriers such as API standardization gaps, data access dependencies, and incumbent banks' strategic resistance. Simultaneously, it underscores emerging opportunities for Fintechs to gain market share and foster innovation. The findings suggest early signs of broader transformation, with both Fintechs and incumbents moving towards platform-based business models. The paper advances our understanding of digital platform regulation and governance and the emergence of digital ecosystems.
Keywords: Market entry; Fintech; Open Banking; Digital platforms; PSD2